Adeno-associated virus 9 vector-mediated cardiac-selective expression of human secretory leukocyte protease inhibitor attenuates myocardial ischemia/reperfusion injury - Podsawee Mongkolpathumrat; Nitirut Nernpermpisooth; Nitirut Nernpermpisooth; Anusak Kijtawornrat; Faprathan Pikwong; Wannapat Chouyratchakarn; Rungrueang Yodsheewan; Sasimanas Unajak; Sarawut Kumphune; Sarawut Kumphune (Frontiers in Cardiovascular Medicine, 2022)
Protease enzymes contribute to the initiation of cardiac remodeling and heart failure after myocardial ischemic/reperfusion (I/R) injury. Protease inhibitors attenuate protease activity and limit left ventricular dysfunction and remodeling. Previous studies showed the cardioprotective effect of secretory leukocyte protease inhibitor (SLPI) against I/R injury. However, overexpression of SLPI gene in cardiovascular diseases has only been investigated in an in vitro experiment. Here, cardiac-selective expression of the human secretory leukocyte protease inhibitor (hSLPI) gene and its effect on I/R injury were investigated. Adeno-associated virus (AAV) serotype 9 carrying hSLPI under the control of cardiac-selective expression promoter (cardiac troponin, cTn) was intravenously administered to Sprague–Dawley rats for 4 weeks prior to coronary artery ligation. The results showed that myocardial-selective expression of hSLPI significantly reduced infarct size, cardiac troponin I (cTnI), creatine kinase-MB (CK-MB), and myoglobin levels that all served to improve cardiac function. Moreover, overexpression of hSLPI showed a reduction in inflammatory cytokines, oxidatively modified protein carbonyl (PC) content, ischemia-modified albumin (IMA), and necrosis and cardiac tissue degeneration. In conclusion, this is the first study to demonstrate cardiac-selective gene delivery of hSLPI providing cardioprotection against myocardial I/R injury in an in vivo model.